Analysis of the Nature and Determinants of Energy Price Dynamics in Sub-Saharan Africa (SSA) - Ifeacho, Christopher I; Choga, Ireen (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2023)
Energy is one of the most important resources needed for growth, and consumption is an indicator to measure the development of a country. Sub-Saharan Africa (SSA) is among the sub-regions in the world with the lowest energy use per capita and one of the reasons for this is the energy price dynamics that have affected energy policy that can engender sustainable economic growth. The main objective of the study is to assess the nature and determinants of energy price dynamics in SSA using 21 countries with a complete dataset between 1980 and 2017 on variables such as energy consumption, exchange rate, and inflation rate, while energy price index and federal fund rate are also included as exogenous variables. EGARCH is used to derive the nature of energy dynamics, while panel-ARDL is used to investigate the determinants of energy price dynamics. The results show that energy price dynamics are asymmetric in nature, while the federal fund rate and exchange rate remain the most important factors influencing energy price dynamics in the sub-region. The finding is contrary to the symmetric energy price obtained by some previous authors who used oil price to proxy energy price. This study used aggregated values of energy prices, which include renewable and non-renewable energy. The implication of the findings is that currency devaluation and rise in federal fund rate aggravate the dynamics in energy piece and this causes much more macroeconomic instabilities in SSA. It is recommended that SSA countries should be cautious to embrace currency devaluation policy, and should reduce dependency on the importation of renewable energy products.